The Effect of Capital Intensity and Leverage on Corporate Tax Aggressiveness in Companies Listed on the Indonesia Stock Exchange with Corporate Governance as a Moderating Variable - Istiqomah; Srikalimah; Fitria Magdalena Suprapto (LP2M IAIN Palopo, 2026)
This research investigates the influence of capital intensity and leverage on corporate tax aggressiveness, while also examining the moderating role of corporate governance in manufacturing firms within the consumer non-cyclical sector listed on the Indonesia Stock Exchange from 2021 to 2024. The study proposes that capital intensity and leverage contribute to tax aggressiveness and assumes that corporate governance may strengthen or weaken these relationships. A quantitative method with an associative research design was applied in this study. The sample consisted of 150 firm-year observations selected through purposive sampling techniques. Secondary data were collected from the annual financial statements published by the companies. The variables were measured using several financial indicators, including capital intensity represented by the ratio of fixed assets to total assets, leverage measured using the Debt to Asset Ratio (DAR), tax aggressiveness measured through the Effective Tax Rate (ETR), corporate governance assessed by the proportion of independent commissioners, and profitability represented by Return on Assets (ROA) as a control variable. Data processing employed panel data regression and Moderated Regression Analysis (MRA) using Python software. The selection of the most appropriate regression model was conducted through the Hausman and Lagrange Multiplier (LM) tests, while descriptive statistical analysis and classical assumption tests were performed using SPSS. The findings reveal that, individually, capital intensity and leverage positively and significantly affect tax aggressiveness. Profitability as a control variable also demonstrates a positive and significant relationship with tax aggressiveness. Simultaneous testing further confirms that both capital intensity and leverage jointly influence tax aggressiveness. Furthermore, the MRA findings indicate that corporate governance does not significantly moderate the relationship between capital intensity and leverage toward tax aggressiveness. These results imply that tax aggressiveness is shaped by multiple internal organizational factors, and the proposed model provides considerable explanatory capability regarding the phenomenon. The findings also suggest that strengthening corporate governance structures alone may not be sufficient to reduce aggressive tax practices unless accompanied by effective implementation. Therefore, companies should improve transparency and accountability in managing tax-related activities, while policymakers are encouraged to reinforce regulations associated with corporate taxation practices. Future studies are recommended to incorporate additional variables, such as company size, liquidity, and audit quality, as well as expand research coverage across different sectors and longer periods of observation to achieve broader and more comprehensive findings.